Evaluating programs aimed at promoting positive youth development: A relational development systems-based view. Issue 3 (2nd July 2016) - Lerner, Richard M.; Lerner, Jacqueline V.; Urban, Jennifer Brown; Zaff, Jon
ABSTRACT: Whether discussing the process involved in positive youth development (PYD), articulating an approach (or philosophy) of youth programs associated with PYD, or enacting a program aimed at promoting PYD, ideas derived from relational developmental systems (RDS) metatheory are pertinent. Accordingly, we discuss the RDS metamodel and explain the approach to PYD research and to PYD program evaluation associated with it. We suggest that the approach to research and evaluation derived from RDS-based ideas offers developmental scientists a set of ideas and tools for research and evaluation methodology that contrast in several ways to methodology associated with different metatheoretical bases. We present a model of program evaluation, termed Evolutionary Evaluation, as a sample case of such an RDS-based approach. We discuss RDS-based approaches to understanding causality and, as well, to using theory-based research and evaluation to promote social justice.